2000
DOI: 10.1007/s005350070045
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cells: a target for the treatment of liver fibrosis

Abstract: Hepatic fibrosis is a wound-healing process that occurs when the liver is injured chronically. Hepatic stellate cells (HSC) are responsible for the excess production of extracellular matrix (ECM) components. The activation of HSC, a key issue in the pathogenesis of hepatic fibrosis, is mediated by various cytokines and reactive oxygen species released from the damaged hepatocytes and activated Kupffer cells. Therefore, inhibition of HSC activation and its related subsequent events, such as increased production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(176 citation statements)
references
References 75 publications
4
171
0
1
Order By: Relevance
“…Whereas HSCs have been generally considered as the major contributor of ECM accumulation in fibrotic livers and thus have been the center of attention as a therapeutic target,37 the present study suggests that the cell types involved in the pathogenesis of liver fibrosis should vary according to its etiology. Thus, careful diagnosis to assess the pathology of liver fibrosis is required for effective targeting and prospective treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Whereas HSCs have been generally considered as the major contributor of ECM accumulation in fibrotic livers and thus have been the center of attention as a therapeutic target,37 the present study suggests that the cell types involved in the pathogenesis of liver fibrosis should vary according to its etiology. Thus, careful diagnosis to assess the pathology of liver fibrosis is required for effective targeting and prospective treatment.…”
Section: Discussionmentioning
confidence: 81%
“…ROS are involved in necrosis and apoptosis of hepatocytes and HSC activation [24,25]. Several major classes of free radical scavengers, such as catalase, superoxide SOD, and glutathione peroxidase (GSH-P), were investigated in various types of liver damage, and they afforded effective protection against the oxidative insults to hepatic parenchyma [26].…”
Section: Hepatic Stellate Cellsmentioning
confidence: 99%
“…27,28 Overexpression of collagen ␣1(I) and consequent formation of excessive and defective extracellular matrix is a hallmark of fibrotic abnormality in response to liver insult. 29,30 We investigated whether the lack of FGF1 and FGF2 affected the induction of hepatic collagen ␣1(I) in response to the acute CCl 4 stimulus. Analysis of steady-state collagen ␣1(I) mRNA expression by RPA showed that in resting livers and those 24 hours after CCl 4 insult, collagen ␣1(I) mRNA was equal in FGF1(Ϫ/Ϫ)FGF2(Ϫ/Ϫ) and WT animals.…”
Section: Decreased Induction Of Matrix Collagen ␣1(i) In Fgf1(ϫ/ϫ)fgfmentioning
confidence: 99%